Percutaneous coronary intervention causes a rapid but transient mobilisation of CD34+CD45− cells. Issue 1 (20th August 2014) - Padfield, Gareth J; Tura-Ceide, Olga; Freyer, Elizabeth; Barclay, G Robin; Turner, Marc; Newby, David E; Mills, Nicholas L
Abstract : Objective: Circulating CD34 + CD45 − cell concentrations are increased in patients with coronary artery disease, however their pathophysiological significance is unknown. We determined CD34 + CD45 − cell concentrations following percutaneous coronary intervention (PCI) in order to explore their role in acute vascular injury. Methods: In a prospective time-course analysis, we quantified using flow cytometry circulating CD34 + CD45 − cells, traditional CD34 + VEGFR-2 + putative endothelial progenitor cells (EPCs), CD14 + VEGFR − 2 + Tie-2 + angiogenic monocytes and intercellular adhesion molecule expression (CXCR-4 and CD18) in patients, before and during the first week following diagnostic angiography (n=13) or PCI (n=23). Vascular endothelial growth factor-A (VEGF-A) and C reactive protein (CRP) were quantified by ELISA. Results: Unlike diagnostic angiography, PCI increased circulating neutrophil and CRP concentrations at 24 and 48 h, respectively (p<0.002 for both). CD34 + CD45 − cell concentrations were unaffected by angiography (p>0.4), but were transiently increased 6 h following PCI (median (IQR) 0.93 (0.43–1.49) vs 1.51 (0.96–2.15)×10 6 cells/L; p=0.01), returning to normal by 24 h. This occurred in the absence of any change in serum VEFG-A concentration, adhesion molecule expression on CD34 + cells, or mobilisation of traditional EPCs or angiogenic monocytes (p>0.1 for all). Conclusions: PCI transiently increases circulating CD34 + CD45 − cells, without increasing CD34 + adhesion molecule expression or VEGF-A concentrations, suggesting that CD34 + CD45 − cells may be mobilised from the vessel wall directly as a result of mechanical injury. Traditional putative EPC and angiogenic monocytes are unaffected by PCI, and are unlikely to be important in the acute response to vascular injury.